Pengaruh Model Pembelajaran Group Investigation terhadap Hasil Belajar IPS Siswa Kelas VIII di SMP Negeri 24 Kota Bengkulu - Ridwan Putra; Irwan Satria; Saepudin Saepudin (Indonesian Journal of Social Science Education (IJSSE), 2024)
This research discusses the influence of the group investigation method on the social science learning outcomes of class VIII students. Here the researcher uses a type of quantitative research which can be interpreted as research based on the philosophy of positivism, used to research certain populations and samples. In preparing this journal the author used an associative approach. One of the factors causing the low learning outcomes of class VIII social studies students is the use of less innovative learning methods. Teachers tend to use the old method, namely delivering learning material using lectures, questions and answers and assignments. As a result, young students feel bored, less interested in learning, resulting in low learning outcomes obtained by students. In this way, the group investigation method can be used as an alternative that will encourage students to be more active in group learning activities. In calculating variables The regression coefficient for the Integrated Social Sciences Learning Using the Investigation Group Method (X) variable is 0.722, meaning that if the value of the other independent variables remains constant and the Integrated Social Sciences Learning Using the Investigation Group Method increases, then learning outcomes (Y) will increase by 0.722. The coefficient is positive, meaning that there is a positive influence of Integrated Social Studies Learning through the Investigation Group Method on the learning outcomes of class VIII students at SMP Negeri 24 Bengkulu City.